2005
DOI: 10.1890/04-0770
|View full text |Cite
|
Sign up to set email alerts
|

Moran Effect on Nonlinear Population Processes

Abstract: I investigate the efficacy of the Moran effect as applied to natural population processes. The Moran effect, the correlated density-independent disturbances that bring independently oscillating local populations into synchrony, was originally conceived as an attribute of a linear model system. However, it applies only approximately to natural populations, as they are inherently nonlinear in their density-dependent structure, given that no animal has an unlimited reproductive capacity. The degree of approximati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 24 publications
3
66
1
Order By: Relevance
“…In contrast, studies of cyclic red grouse populations in five different regions in northern England showed that climatic conditions in May and January can force the populations within each region to oscillate in synchrony (Cattadori et al 2005). This study does not report any travelling wave phenomena and instead suggests that, in these red grouse populations, cycles are synchronized by a Moran effect (Koenig 2002;Royama 2005). The differences in the findings of these two studies may be due in part to differences in the scale and the type of analysis.…”
Section: Empirical Evidence For Travelling Wavescontrasting
confidence: 70%
“…In contrast, studies of cyclic red grouse populations in five different regions in northern England showed that climatic conditions in May and January can force the populations within each region to oscillate in synchrony (Cattadori et al 2005). This study does not report any travelling wave phenomena and instead suggests that, in these red grouse populations, cycles are synchronized by a Moran effect (Koenig 2002;Royama 2005). The differences in the findings of these two studies may be due in part to differences in the scale and the type of analysis.…”
Section: Empirical Evidence For Travelling Wavescontrasting
confidence: 70%
“…However, the cross-correlation of population density was consistently smaller than that of the environmental driving, r p or. This finding confirms results from field and theoretical studies 12,19,20,23 .…”
Section: Resultssupporting
confidence: 91%
“…Given that environmental fluctuations can be spatially correlated over large distances, the Moran effect was considered as a major mechanism for generating population synchrony under natural [9][10][11][12][13][14] and laboratory conditions [15][16][17] . It was generalized to include nonlinear density dependence, populations in nonidentical habitats, the influence of dispersal, cyclic populations, species interactions and various combinations of these factors 9,12,[18][19][20][21][22][23] . All these studies found that the correlation of independent populations, not coupled by dispersal, remains bounded by the environmental correlation, r p rr, which should limit the Moran effect as a driver of population synchrony.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Synchrony is the consequence of two independent factors: the dispersal of populations among patches and the existence of common meteorological driving forces (Moran effect). The theory is well established; see [10,29,42] for dispersal, [54] for the Moran effect, and [16] for the mixed case.…”
Section: Introductionmentioning
confidence: 99%